ASSESSMENT OF THE IMPACT OF BREAKWATER ON EROSION-DEPOSITION PROCESSES IN TAM QUAN RIVER MOUTH, BINH DINH PROVINCE - Anh, Vu Tuan (Vietnam Journal of Marine Science and Technology, 2018)
After the establishment of breakwater at Tam Quan river mouth in 2009, this area has been deposited quickly, especially in the rainy season (coinciding with northeast monsoon). The processes of litho-hydrodynamics and erosion-deposition change clearly over seasons. In the rainy season (September to December) prevailing wind directions are NE, NNE, N and NW. Most wind speeds range from level 2 to level 5. Waves generated by NE, N winds have the most impact on the Tam Quan river mouth. During propagation into the channel the waves reduce rapidly and tend to push the bed material from the sea to the channel that causes the alternate deposition and erosion in the river mouth and channel. Currents carry bed material from the river to the sea and cause the alternate deposition and erosion in the channel. Bed materials are accumulated in an arc-shaped area around the mouth. In the dry season (January to August) prevailing wind directions are SE, SSE and S, and wind speeds are rather small, from level 2 to level 4. The E wind has a low frequency but generates waves that cause direct impacts on the studied area. The wave height reduces rapidly during transmitting into the channel. The waves generated by the SE wind tend to push bed material from the sea and around Truong Xuan cape to the channel, then accumulating in the mouth. Wave-currents formed along the northern shore bring the materials to accumulate in the channel center. Currents just cause bed materials to move at the time of strong ebb-tide and then accumulate on a large area at the mouth, but with negligible intensity. Calculation results of the bed evolution from 15/12/2014 to 20/5/2015 fairly correspond with the measured results. This is the scientific basis of the solutions for long-term stability of channel.